Cenozoic inversion of the East China Sea Shelf Basin: Implications for reconstructing Cenozoic tectonics of eastern China - Su, J.; Zhu, W.; Chen, J.; Ge, Rongfeng; Zheng, B.; Min, B. (Taylor & Francis Inc., 2014)
The structural styles of the East China Sea Shelf Basin are described based on the interpretation of seismic profiles. The basin is divided into West and East Rift regions. It has undergone four phases of compressive structural inversions during the late Palaeocene Oujiang Event, the late Eocene Yuquan Event, the early Miocene Huagang Event, and the latest Miocene Longjing Event. Structural inversions have superimposed on the Cenozoic extensional rift basin during these compression events, forming regional unconformity reflectors (T4°, T3°, T2°, and T1°). The Changjiang Depression located in the north of the West Rift Region is characterized by a number of NW-, EW-, to NE-trending faults. However, the other depressions in the East China Sea Shelf Basin are dominated by NNE-to NEE-trending faults. During the Palaeocene, the Taibei Depression was in a marine environment, whereas the Changjiang Depression was terrestrial, although both depressions are located in the West Rift Region. The Hongzhouwan-Okinawa Fault separates the East China Sea Shelf Basin into south and north. The structural styles and the sedimentary environment change longitudinally and transversely, which are controlled by basement structures. The depocentre of the East China Sea Shelf Basin has gradually migrated and became younger from west to east. The structural inversion also becomes younger from west to east, but the intensity of inversion increases from south to north. These structural inversion events reveal a periodic compression and imply that the compressive uplift of eastern China resulted from subduction of the Pacific Plate as well as collision of the Luzon arc and the Asian continent rather than the remote effect of India-Asian collision.